2011
DOI: 10.1016/j.adolescence.2011.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in adolescence: Examining the role of recent adverse experiences

Abstract: Although there is a well-known link between adverse experiences and suicidal ideation, there has been little study of the effects of recent adverse experiences on suicidal ideation in teenagers. This study examined the association between recent adverse experiences and suicidal ideation in a sample of 740 at-risk 16-year-old youth in the LONGSCAN studies, as well as potential mediators. 8.9% of the youth reported suicidal ideation. Recent adverse experiences, as a class, were associated with suicidal ideation;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 67 publications
(110 reference statements)
5
77
1
5
Order By: Relevance
“…In a follow-up of over 25 years, they found that adolescents with suicidal ideation were, at the age of 30, more than twice as likely to suff er from an Axis I disorder, about 12 times more likely to attempt suicide, and presented low self-esteem, signifi cant interpersonal problems and impaired overall functioning. Simultaneously, these individuals seemed to experience more negative events throughout life (Horesh, Nachshoni, Wolmer, & Toren, 2009;Liu & Tein, 2005;Thompson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up of over 25 years, they found that adolescents with suicidal ideation were, at the age of 30, more than twice as likely to suff er from an Axis I disorder, about 12 times more likely to attempt suicide, and presented low self-esteem, signifi cant interpersonal problems and impaired overall functioning. Simultaneously, these individuals seemed to experience more negative events throughout life (Horesh, Nachshoni, Wolmer, & Toren, 2009;Liu & Tein, 2005;Thompson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Girls reported significantly higher rates of somatic than did boys while aggresive and delinquent behavior higher than girls (Reynolds, O'Koon, Papademetriou, Szczygiel, & Grant, 2001). Recent stressful life events, especially physical and psychological abuse, significantly predicted suicide ideation in youth, even after controlling for a host of other risk factors (Beautrais, 2003;Thompson, Proctor, English, Dubowitz, Narasimhan, & Everson, 2011;Zhang, Wang, Xia, Liu, & Jung, 2012).…”
Section: Sle On Adolescentsmentioning
confidence: 97%
“…8 The effects of trauma during childhood and adolescence have impacts on adolescent health and educational status, including a greater likelihood of repeating a grade in school, lower resilience, increased risk for learning and behavioral issues, suicidal ideation, and early initiation of sexual activity and pregnancy. 5,[8][9][10] In fact, there is a much higher prevalence of these negative impacts among adolescents aged 12 to 17 after experiencing more than one ACE. With 3 or more ACEs, nearly half (48%) of youth experience low engagement in school, 44% cannot stay calm and controlled, and 41% demonstrate high externalizing behaviors.…”
Section: Prevalence and Impacts Of Aces In Adolescencementioning
confidence: 99%